The Epidemiological Pattern of Injuries among Children under 15 Years of Age in Fasa in 2013 - Farzaneh Mobasheri; Hadi Azizi; Fahimeh Rastbaf (Fasa University of Medical Sciences, 2016)
Background & Objectives: Every year millions of children die due to injuries. Since children are vulnerable to injuries, appropriate measures must be taken to prevent injuries in this group. To achieve this goal, it is vital to recognize the epidemiological patterns of injuries. The purpose of this study is to determine the frequency and characteristics of child injuries in Fasa (Fars, Iran) so as to direct the local and national health authorities' attention towards controlling and preventing child injuries. Materials & Methods: This cross-sectional study was conducted in 2013 on 1245 children between 0-14 years of age suffering from injuries who referred to Vali-Asr Hospital. The data were extracted from the national software injuries registry program. They were analyzed by Chi-square test, Fisher exact test, and Independent T-Test, using SPSS19 software. Results: This study showed that 1245 children were injured in 2013 (mean age of 6.5 ± 1.4 years). The majority of the injured were boys (62%) and two-year-old children (11.1%). Most of the injuries happened in urban areas (58.9%), in winter (33.8%), and at home (65.9%). Moreover, trauma (34.9%), falling (31.3%), and poisoning (16.1%) were more common in comparison to other injuries. Intentional and domestic injuries were significantly higher in girls (p = 0.039 and p < 0.001; respectively). Conclusion: According to the results, the priority of child injuries includes trauma, falling, and poisoning. Thus, these injuries should be considered in planning for the preventive measures of child injuries.